ATTITUDE OF THE SCHOOL OF FINE ARTS AND SPORTSCHOOLS STUDENTS IN THE SPORT DEPARTMENTS TOWARDS THE QUANTITATIVE CLASSES (SAMPLE ELAZIĞ) - Eyüp GENÇ (Fırat University, 2019)
Attitudes and behaviours are usually considered as a positive or negative attitude towards an object which is dealt with, a situation or an event of any person. And the education in this context, however, can be expressed as a process of taking forward the in